2016
DOI: 10.1159/000452428
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Progenitor Cells Affect Thrombosis of Dialysis Arteriovenous Fistulas

Abstract: Background: Arteriovenous fistula (AVF) thrombosis is a relevant cause of morbidity in hemodialysis (HD) patients. The number of circulating endothelial progenitor cells (EPCs) has been identified as a surrogate marker for vascular repair and health. Deficiency of EPCs has been demonstrated in dialysis patients to be associated with vascular events. Nonetheless, their role in thrombosis of AVFs remains unknown. Methods: From January 2010 to May 2013, 147 HD patients with dysfunctional AVFs were enrolled. Surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Delayed reendothelialization secondary to decreased endothelial cell proliferation and migration is related to increased risk for delayed thrombosis observed after endovascular therapy in CKD patients [37,38]. This is especially relevant to CKD patients, as adequate vascular access sites for hemodialysis (HD) often serve as their lifeline, and these sites are especially susceptible to thrombosis in the setting of repeated endothelial injury [39][40][41].…”
Section: Alteration Of the Procoagulant Function Of Endothelial Cellsmentioning
confidence: 99%
“…Delayed reendothelialization secondary to decreased endothelial cell proliferation and migration is related to increased risk for delayed thrombosis observed after endovascular therapy in CKD patients [37,38]. This is especially relevant to CKD patients, as adequate vascular access sites for hemodialysis (HD) often serve as their lifeline, and these sites are especially susceptible to thrombosis in the setting of repeated endothelial injury [39][40][41].…”
Section: Alteration Of the Procoagulant Function Of Endothelial Cellsmentioning
confidence: 99%
“…In CKD patients, endothelium dysfunction begins in the early stages of CKD [ 42 ] and takes a substantial part in thrombotic events [ 43 ]. In hemodialysis patients, endothelial injury is associated with an increased risk of AVF thrombosis [ 44 , 45 , 46 ]. The modifications of hemodynamic stress in vascular access and the accumulation of uremic toxins play a major role in endothelium dysfunction [ 45 ].…”
Section: Thrombotic Mechanisms Induced By Tryptophan-derived Uremimentioning
confidence: 99%
“…Endothelial progenitor cells have been shown to mobilize and incorporate into the denuded vessel wall, a process associated with accelerated re-endothelialization [ 61 ]. Clinical studies have shown progenitor cell deficiency to be associated with restenosis and thrombosis after endovascular intervention [ 62 , 63 , 64 ]. Indoxyl sulfate has a deleterious effect on progenitor cell function, which may precipitate thrombosis through delayed re-endothelialization [ 36 ].…”
Section: Indoxyl Sulfate and Thrombosis Of Dialysis Vascular Accesmentioning
confidence: 99%